ANALISIS KONFLIK TOKOH UTAMA DALAM NOVEL PUBER KARYA RIO RINALDO - Noni Anjeli; Christanto Syam; Sesilia Seli (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe general problem of this research was conflict analysis in the main character in a novel entitled Puber by Rio Rinaldo which tells the story of a teenage girl with all kinds of problems she faces both external conflicts and internal conflicts in her family and her school environment. The problems in this study were: (1) external conflict in the main character, (2) internal conflict in the main character, (3) implementation of learning Indonesian language and literature in school learning about external and internal conflicts. The purpose of this study was to examine external conflicts and internal conflicts of the main characters. This study used the study of literary psychology, a method of description with qualitative research. Data from this study were sentences that indicate the external and internal conflicts of the main characters. The technique used in this study was documentary study, and the data collection tool was the researcher himself as a key instrument. Based on the results of data analysis there were 4 external conflict data and 10 internal conflict data in a novel entitled Puber written by Rio Rinaldo. The implementation of this research was realized in the form of RPP. Keywords: conflict. main character, novel